2020
DOI: 10.14527/pegegog.2020.030
|View full text |Cite
|
Sign up to set email alerts
|

Design thinking: Opinions and experiences of middle school students

Abstract: The aim of the present research is to examine the opinions and experiences of 7th grade students towards design thinking. In this context, activities for design thinking about energy transformations included in the science curriculum were conducted for four weeks. Phenomenology method, one of the qualitative research methods, was used in the study carried out with thirty-six 7th grade students. The students' opinions about design thinking were obtained through open-ended questions and their experiences through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Certainly, there must be the perception that Design Thinking is no longer an uncommon practice in education and that everyone is used to employing it as a problem-solving strategy. Nonetheless, Çiftçi & Topçu (2020) remarked that there are limited studies on the implementation of Design Thinking in education. This suggests that educators are still hesitant to apply Design Thinking despite findings from literature reviews by Panke (2019) showing how infrequently bad results are reported in Design Thinking case studies.…”
Section: Design Thinking: a Privileged Approachmentioning
confidence: 99%
“…Certainly, there must be the perception that Design Thinking is no longer an uncommon practice in education and that everyone is used to employing it as a problem-solving strategy. Nonetheless, Çiftçi & Topçu (2020) remarked that there are limited studies on the implementation of Design Thinking in education. This suggests that educators are still hesitant to apply Design Thinking despite findings from literature reviews by Panke (2019) showing how infrequently bad results are reported in Design Thinking case studies.…”
Section: Design Thinking: a Privileged Approachmentioning
confidence: 99%
“…As a differentiation strategy, design thinking can be applied in different contexts such as science education (Atacan, 2020;Çiftçi & Topçu, 2020;Lee, Yoon & Kang, 2014), graphic design (Duman & Kayalı, 2017), social studies education (Aydemir & Çetin, 2021;Koh et al, 2015), teacher education (Carroll, 2014;2015;Odabaşı et al, 2018;Öztürk, 2020), programming education (Avcu & Er, 2020), STEM education (Arifin & Mahmud, 2021;Avcu & Ayverdi, 2021;Hsiao et al, 2017;Li et al, 2019;Sarıkoç & Ersoy, 2022;Simeon, Samsudin & Yakob, 2022), educational game design (Caferoğlu, 2021), drama education (Polat &Bayram, 2021). Design thinking has been used in many studies concerning the education of gifted students.…”
Section: Figure 1 Differentiation Concept Mapmentioning
confidence: 99%